Memaknai Ulang Wacana Waria dalam Konteks Indonesia (Analisis Hermeneutika Terhadap Novel “Perempuan Tanpa V”) - Muhammad Syafi’i (UIN Sunan Kalijaga Yogyakarta, 2018)
The social construction of transvestites which has so far been still far from what is expected, transgenders in general often get stereotypes that have long taken root so that they become individuals/groups who are marginalized in society. They tend to be shunned because religion and morality are big questions due to their tendency to like same-sex. This construction is entrenched and to this day, they have not received a proper place and are made as human beings as usual. Related to this, there is a novel called